PENGARUH ALOKASI PEMBEBANAN PAJAK PENGHASILAN ANTAR PERIODE TERHADAP KOEFISIEN RESPON LABA - Endang Kiswara (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2009)
Abstract Inter period tax allocation is noise factor of earnings content of financial statements. Earnings is important component of taxable income assessment that difference from accounting treatment. This research investigate effect of inter period tax allocation toward earnings response coefficient (ERC). Research conducted for 38 samples companies from any industries that going public at Indonesia Stock Exchange 1997 to 2004. Data is analyze by multiple regression, and t-test. Output of this research stated that ERC before and after tax allocation based on PSAK 46 are the same, at significance value 0,404. This implied that inter period tax allocation is not having impact on ERC, at significance value 0,489. This researchfound that usefulness of accounting for income tax based on PSAK 46 is not difference with the non applicant.Keywords: Earnings Response Coefficient (ERC), inter period tax allocation,deferred tax expense, deferred income tax.